2016
DOI: 10.17221/89/2015-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Production of tetraploid plants of Trollius chinensis Bunge induced by colchicine

et al.

Abstract: Zhang Q., Zhang F., Li B., Zhang L., Shi H. (2016): Production of tetraploid plants of Trollius chinensis Bunge induced by colchicine. Czech J. Genet. Plant Breed., 52: 34-38.Trollius chinensis Bunge is one of the important ornamental and medicinal plants cultivated in China. In this study, the tetraploid plants of Trollius chinensis were successfully induced by colchicine and their morphological, cytological and fertility characteristics were investigated. The results indicated that the tetraploid species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This result revealed that inflorescences diameter of Calendula plants increased as concentration rate of colchicine increased and reached its peak values at 0.05 per cent. Similar results were reported by various authors as (Zhang et al, 2016) on Trollius chinensis (Wang et al, 2017) on Fagopyrum tataricum and (El-Nashar and Ammar 2016) on C. officinalis. They found that colchicine treatments had a positive and significant effect on diameter of inflorescences compared to untreated plants.…”
Section: Diameter Of Inflorescencesupporting
confidence: 91%
“…This result revealed that inflorescences diameter of Calendula plants increased as concentration rate of colchicine increased and reached its peak values at 0.05 per cent. Similar results were reported by various authors as (Zhang et al, 2016) on Trollius chinensis (Wang et al, 2017) on Fagopyrum tataricum and (El-Nashar and Ammar 2016) on C. officinalis. They found that colchicine treatments had a positive and significant effect on diameter of inflorescences compared to untreated plants.…”
Section: Diameter Of Inflorescencesupporting
confidence: 91%
“…It also informed that the stomata size of the tetraploids larger but less than diploid plants [ 4 , 21 ]. In comparison with diploid plants, the tetraploids showed an increase not only in the stomatal size but also the chloroplast numbers in guard cell [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, colchicine reduced the plant height of Impatiens balsamina at three weeks after planting while plant stem diameter increased [ 35 ]. The tetraploid plants achieved by colchicine treatment showed an increase in phenotypic features such as leaf length and width, petiole, flower, and pollen diameters, but decreased in the pollen fertility [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Addition of 0.01 % of colchicine could induced polyploidy in Bacopa monnieri [26] and mixoploidy in Physalis peruviana L. [27]. Furthermore, addition of 0.1 % colchicine in Trollius chinensisis thought to be optimal to induce the polyploid plants [28].…”
Section: Ploidy Level Identificationmentioning
confidence: 98%